A combined experimental and computational study of the esterification reaction of glycerol with acetic acid - Bedogni, Gabriel Alejandro (2014)
This work describes theoretical and experimental studies on glycerol esterification to obtain acetins focusing on the obtained isomers. The reaction of glycerol with acetic acid was carried out on Amberlyst 36 wet. Density functional theory calculations on the level of M06-2X functional and 6-311+G(d,p) basis set are carried out and the most stable structures of the reactants and products are located by considering a large number of conformers. The thermodynamics is discussed in terms of the calculated reaction Gibbs free energy. The AIM theory was used to characterize reactants and products. The glycerol esterification with acetic acid is found to be thermodynamically favored, with exothermal property. These agree well with experiments and allow us to explain the relative selectivity of products.